Radionuclide study in gastroparesis: Is it still relevant? - Abdul Rahim, Mohamad Shahrir; Shuaib, Ibrahim Lutfi; Ahmad Sarji, Sazilah (International Islamic University Malaysia, 2016)
The incidence of gastroparesis in Malaysia is not well documented. It is diagnosed based on clinical symptoms and exclusion of the obstruction. Here a case of a young adult woman with type 1 diabetes mellitus suffering severe gastrointestinal symptoms. In this case, radionuclide scintigraphy is used as one of the investigation to confirm the diagnosis of gastroparesis.